Plasticity of Boronized Layers - Krukovich, M. G.; Prusakov, B. A.; Sizov, I. G. (Springer Series in Materials Science,, 2016)
This book presents the physico-technical basis and current state of the technology of boronized layers. Special attention is given to the layer structure and morphology of allocated phases and distributions in a superficial zone of chemical compounds. Two- and multi-component phases of alloys and diffusion processes in a self-organizing mode are discussed. Surface hardening by boronizing increases the life time of mechanical tools. This is important for the mining industry, agriculture, textile and chemical industry. The book is important for thermochemical treatment and surface hardening of metals and alloys.